2010
DOI: 10.1590/s1806-37132010000400008
|View full text |Cite
|
Sign up to set email alerts
|

Risco aumentado de sintomas respiratórios e bronquite crônica em mulheres que utilizam biocombustíveis na Nigéria

Abstract: Objective: To determine whether respiratory symptoms and chronic bronchitis are associated with the use of biomass fuels (BMFs) among women residing in rural areas of the Ekiti State, in southwestern Nigeria. Methods: From January to June of 2009, we carried out a cross-sectional study including 269 adult women. To collect data on sociodemographic status, type of fuel used for cooking in the household, respiratory symptoms, and smoking history, we used a questionnaire adapted from the European Community Respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 21 publications
(25 reference statements)
4
12
1
Order By: Relevance
“…While there are no comparable studies among HIV-infected populations in sub-Saharan Africa, two recent studies measured the odds of cough among biomass-exposed populations in Malawi [13] and Nigeria [14]. Similar to our work, both studies identify increased odds of cough among females cooking with firewood.…”
Section: Discussionsupporting
confidence: 82%
“…While there are no comparable studies among HIV-infected populations in sub-Saharan Africa, two recent studies measured the odds of cough among biomass-exposed populations in Malawi [13] and Nigeria [14]. Similar to our work, both studies identify increased odds of cough among females cooking with firewood.…”
Section: Discussionsupporting
confidence: 82%
“…Increased hygiene reduces exposure to allergens and decreases natural desensitization (21). The exposure to external agents can result in the development of COPD, which is mainly associated with occupational activities, such as coal and gold mining (22), cadmium mining (23) and exposure to smoke from burning wood (24),(25). Regarding bronchiectasis, exposure to fungi is a cause of exacerbated allergic responses, such as in allergic bronchopulmonary aspergillosis (15).…”
Section: Introductionmentioning
confidence: 99%
“…In another study which examined the impact of use of biomass fuel on respiratory symptoms using a cross-sectional design, Desalu et al , reported that the use of solid fuels like wood constitutes a high risk for respiratory symptoms, especially cough and sputum 14. They showed that women using wood were five times more likely to report cough and four times more likely to have chronic bronchitis compared with those using gas or kerosene.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have investigated the relative impact of different domestic fuel types on respiratory symptoms and lung function in sub-Saharan Africa 13141516. Firewood and kerosene are used frequently in many sub-Saharan rural homes as major sources of domestic energy; however, their effect on respiratory symptoms or lung function among Nigerians is not well understood.…”
Section: Introductionmentioning
confidence: 99%